Selective Activation of CCl and CF Bonds by SO.+ Radical Cations: An Experimental and Computational Study. Issue 9 (16th July 2013) - de Petris, Giulia; Troiani, Anna; Rosi, Marzio; Angelini, Giancarlo; Ursini, Ornella
Abstract The activation of C–halogen bonds by the SO.+ radical cation is investigated in the gas phase. The CCl bond of CH2Cl2 is activated by fast and effective chloride‐ion transfer, whereas the CF bond of CH2F2 is activated by a very slow fluoride‐ion transfer. In both cases, thermodynamic and kinetic factors account for the type of process and the observed selectivity, that is, carbon–halogen versus carbon–hydrogen activation, mainly owing to the presence of the sulfur atom. The cleavage of the CCl bond of CH2Cl2 by SO.+ is a rare example of a very effective and selective chloride‐ion abstraction by a metal‐free, sulfur‐centred radical cation.